Synthesis, Characterization, X-Ray Diffraction Studies and Biological Properties of Ni(II) and Pd(II) Complexes of Tetradentate Schiff Bases - Shaikh, Julekha A. (Asian Journal of Chemistry, 2018)
Ni(II) and Pd(II) complexes of ONNO type tetradentate Schiff bases derived from 2:1 molar condensation of o-phenylenediamine and substituted salicylaldehydes have been synthesized and characterized by physico-chemical techniques such as elemental analysis, magnetic susceptibility measurements, conductivity measurements, electronic, IR, 1H NMR spectral studies as well as X-ray diffraction studies. Analytical data suggest 1:1 (metal:ligand) stoichiometry of the metal complexes. The molar conductance data revealed the non-electrolytic behaviour of the complexes. Comparison of spectral data of Schiff bases and their metal complexes indicate that the Schiff bases act as dibasic tetradentate ligands and are coordinated to the metal ions via azomethine nitrogen and deprotonated phenolic oxygen atoms. Magnetic susceptibility and electronic spectral data confirm the diamagnetic nature and square planar geometry for the complexes. The powder X-ray diffraction data suggested monoclinic crystal system for these complexes. The ligands and their metal complexes have been screened for antimicrobial activities.